Kooperations- und Organisationsformen für Stadtregionen - beispiele aus Deutschland - Scheller, Jens Peter (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2003)
City regions Starkenburg, Hannover and Frankfurt on Main are set as examples on the basis of which the author represents organisational and substantive forms of cooperation of science and "conjuncture policy" when planning development of these cities. Necessity for the equalisation of living conditions of city and countryside, relationships between city and state and relationships between certain regions of different development stages, are pointed out.
Keywords: Germany; mesta; Nemčija; regije; regionalni razvoj; regionalno planiranje; suburbanizacija; urbana geografija